AAV5 delivery of CRISPR-Cas9 supports effective genome editing in mouse lung airway - Shun‐Qing Liang; Christopher J. Walkey; Alexa Martinez; Qin Su; Mary E. Dickinson; Dan Wang; William R. Lagor; Jason D. Heaney; Guangping Gao; Wen Xue (2021)
Genome editing in the lung has the potential to provide long-term expression of therapeutic protein to treat lung genetic diseases. Yet efficient delivery of CRISPR to the lung remains a challenge. The NIH Somatic Cell Genome Editing (SCGE) Consortium is developing safe and effective methods for genome editing in disease tissues. Methods developed by consortium members are independently validated by the SCGE small animal testing center to establish rigor and reproducibility. We have developed and validated a dual adeno-associated virus (AAV) CRISPR platform that supports effective editing of a lox-stop-lox-Tomato reporter in mouse lung airway. After intratracheal injection of the AAV serotype 5 (AAV5)-packaged S. pyogenes Cas9 (SpCas9) and single guide RNAs (sgRNAs), we observed ∼19%-26% Tomato-positive cells in both large and small airways, including club and ciliated epithelial cell types. This highly effective AAV delivery platform will facilitate the study of therapeutic genome editing in the lung and other tissue types.